Challenges faced by the state- funded rural women’s co-operatives in reducing poverty in the Mbhashe area, Eastern Cape Province - Lombard, A. (Antoinette) (University of Pretoria, 2014)
Dissertation (MSW)--University of Pretoria, 2013.